Problems in prawn culture. - Shigeno, Kunihiko (New Delhi Amerind Publ. Co., 1978)
Aquaculture series ; no. 19
Keywords: Kuruma shrimp; PENAEUS JAPONICUS; Shrimps; Japan; Kuruma shrimp culture--Japan.; Shellfish culture--Japan.